Atratividade e gênero da carreira docente no Brasil - Pedro Menezes Vilarinhos (2019)
While international evidences show that the countries that have the best educational results are the ones that select their top students into the teaching career, Brazil goes the other way. Data from 2015 show that students that are interested in becoming teachers are amongst the worst performing ones in High School. Additionally, the fact that teaching is, historically, a predominately female occupation – at least since 1997 about 83% of the primary teachers in Brazil are women – also draws attention. This study’s main objective is to analyze, together, both facts mentioned above. First we analyze, separately, the difference between teachers and other occupations’ hourly wages; and the difference for women and men in 1996 and 2016. After that, interactions of these two analysis were made in order to explore the differential inside each group – occupational and male/female – and between the groups. For this purpose, Oaxaca-Blinder’s (1973) methodology was applied to the Annual Relation of Social Information’s (RAIS) microdata of 1996 and 2016. The results show that teaching is more attractive to women than to men but it also shows that this scenario is slowly changing. The hypothesis here is that teaching is no longer being seen as woman’s job because of the requirement of a college degree for primary teachers. This change in the requisites made the teaching career loose a bit of its connection to the maternal and care characteristics, making it more “adequate” to men. Even though this is an ongoing process, the fact is that women still represent the vast majority of the Brazilian primary teachers and, in this career, still get paid less than their male colleagues and women in other occupations. In order for the teaching career to become more attractive to capable and qualified persons – whatever the sex is – it is necessary to value the ones that are already there.